Análise do desenvolvimento gonadal de Pimelodus britskii Garavello & Shibatta, 2007 (Siluriformes – Pimelodidae) de primeira geração (F1) mantidos em cativeiro - Oliveira, Juliano Karvat de (2019)
The reproduction is considered one of the most important aspects of the biology of a species and presents a series of characteristics that may undergo variations in response to environmental conditions. In addition, species with potential for fishing and cultivation have been affected by factors such as anthropological action, deforestation of riparian forests, overfishing and destruction of environments for reproduction and development of larvae and juveniles. In view of this, captive production is an alternative for the reduction of fishing pressure on natural stocks. However, although advances in the development of techniques for the production of juveniles in large scale are successful in aquaculture in Brazil, they do not include all species. For this reason, it is necessary to study the reproductive development of fish farmed in captivity. In this sense, this work aims to analyze the gonadal development and reproductive activity of Pimelodus britskii, first generation (F1) kept in captivity. For this study 227 individuals (131 males and 96 females) were used, from the first generation (F1), from six months of age and the biometric parameters (weight and standard length) and reproductive parameters were evaluated (Gonadosomatic Relation and histological analysis of the gonads). Males and females showed gradual weight gain and growth during the follow-up months. Regarding gonadal development, sexually immature males and females were found in the first months of observation, which correspond to low IGS values. The development of male and female gonads, observed microscopically, through histological analysis, were proportional to the variations of the IGS increase, and the highest values occurred in November and December, indicating the seasonal influence on the gonad maturation process.